Modelling the survival of an Escherichia Coli in Soil : effect of pH and temperature - Ling, Teck Yee; Kasing, Apun; Jong, Hse Jun (3rd Federation of Asia-Pacific Microbiology Societies Conference, Kuala Lumpur 15 - 18 October 2003, 2003)
Survival of E.coli on soils determines its the availability for transport during rainfall events. In this study, the survival of E.coli in soil was examined under different pH in saturated condition. Results indicated that first order decay model fit well. Decay rate of E.coli increased when pH of the soil decreased from 7.4 to 3.2 and also when temperature increased from 20 Degree Celsius to 30 Degree Celsius. Survival was prolonged in neutral and cool condition. There is no significant difference between decay rate at pH of 6.4 and 7.4. At pH of 6.4 and 7.4 at 30 Degree Celsius and at pH 7.4 at 20 Degree Celsius, there was evidence of regrowth. Quantitative relationships between decay rate and pH at 20 Degree Celsius and 30 Degree Celsius were developed for use in environmental modeling purposes.